Limno-terrestrial Diatom Flora in Two Stream Valleys Near Arctowski Station, King George Island, Antarctica - Noga, Teresa; Kochman-Kędziora, Natalia; Olech, Maria; Van de Vijver, Bart (Polish Polar Research, 2020)
Diatom communities sampled in the vicinity of the Polish Antarctic Arctowski Station (King George Island, South Shetland Islands) have been investigated. Soil and sediment samples were collected from Petrified Forest Creek and Ornithologist Creek valleys. A total of 98 diatom taxa belonging to 30 different genera were recorded in the counts. Nine taxa have a marine origin but all together constitute only 0.14% of all counted valves. Three species: Staurosira pottiezii, Psammothidium germainioides and Sellaphora jamesrossensis dominated the flora. Some differences in the diatom assemblages were observed between soil samples from two stream valleys and between soil and sediments from the same catchment area. The highest species diversity was recorded in samples from the dried-up bed of the Ornithologist Creek, where both freshwater and terrestrial species were found. The soil samples from both investigated valleys showed a comparable number of species, but a different species composition. Based on the PCA analysis a clear separation of the assemblages from both creeks could be observed.